APP Incluir: acessibilidade cultural no museu Casa de Aluizio Campos - Nascimento, Vanessa Vera do (2021)
The development of actions that promote accessibility for people with disabilities and new audiences in cultural spaces, including museums, is a search that has become increasingly present and growing in the area of culture and heritage preservation. One of the ways to promote cultural change in the methods of preservation and dissemination of the heritage of these organizations is to develop accessible actions. In this research, we aim to promote the cultural accessibility of people with disabilities at the Museu Casa de Aluízio Campos through the development of an application with accessibility features. During this investigation, we developed the software for the Inclur application, using the Java language through the Android Studio platform, in addition to promoting a reflection on the importance of cultural accessibility in MCAC. Insert the central concepts used in the research, citing authors and sources. As for the technical procedure, suggestions for methods and research activities will basically be centralized in Design Science Research (DSR). According to Dresh, Lacerda and Júnior (2015), the DSR is a method that operationalizes the conduct of studies when the objective to be achieved is a product or a prescription, that is, design guidelines or recommendations. The participation of people with disabilities and representatives of new audiences in accessible curatorship proposals results in a change in languages and traditional production models, enabling knowledge and dialogue with the needs and concerns of these individuals through protagonism and the creation of new projects such as the “Inclur” application, which at the time of writing this work already had its base built and five works inserted to illustrate its purpose. In addition to raising reflections on accessibility not only in the museum, but in schools, since in one of the technical visits to the MCAC, we were invited to visit a public school located in the Aluizio Campos housing complex, to discuss ideas on how to work with accessibility at school.